Can blood flow restriction augment muscle activation during high‐load training?. (16th January 2017) - Dankel, Scott J.; Buckner, Samuel L.; Jessee, Matthew B.; Mattocks, Kevin T.; Mouser, J. Grant; Counts, Brittany R.; Laurentino, Gilberto C.; Loenneke, Jeremy P.
Summary: Introduction: Blood flow restriction has been shown to augment muscle activation and increase muscle size when combined with low‐load training; however, much less is known on whether blood flow restriction can augment muscle activation during high‐load exercise. Purpose: To determine whether applying blood flow restriction can augment muscle activation with traditional high‐load resistance exercise. Method: Ten individuals completed two sets of elbow flexion exercise to volitional fatigue. The control arm rested for 3 min between sets while the experimental arm had blood flow restriction applied for 3 min. Result: The blood flow restricted arm completed significantly fewer repetitions in set 2 in comparison with set 1 [set 1: 9 (1), set 2: 4 (1); P <0·001], whereas no meaningful differences were observed in the control arm [set 1: 8 (1), set 2: 7 (1); P  = 0·057]. There was no interaction for muscle activation ( P  = 0·851) with both conditions significantly lower at the start of set 2 [87 (26)%] in comparison with the end of set 1 [106 (40)%] or end of set 2 [103 (33)%]. Conclusion: The application of blood flow restriction does not augment muscle activation present with high‐load exercise and would seem unlikely to induce greater muscle hypertrophy.